Timing of Breeding Reveals a Trade-Off between Immune Investment and Life History in Tree Swallows. (13th May 2022) - Chang van Oordt, David A; Taff, Conor C; Ryan, Thomas A; Vitousek, Maren N
Synopsis: The allocation of limited resources among life history traits creates trade-offs that constrain the range of possible phenotypes of organisms. In animals, the cost of maintaining an effective immune response may reduce the ability to invest in reproduction, resulting in altered susceptibility to disease. However, not all members of a population face identical constraints because differences in an individual's environmental context or physiological state can influence the degree to which traits are negatively associated. Here, we evaluated how variation in timing of breeding, a correlate of fitness, may result in different patterns of trait associations between immunity and reproduction. We measured constitutive immunity in breeding female tree swallows ( Tachycineta bicolor ) using a bacteria killing assay with blood plasma to assess the relationships between bacteria killing ability (BKA), reproductive effort, and reproductive success. We found that timing of breeding can influence the association between BKA and reproductive effort, but its effects are not homogeneous among all traits. Late-breeding tree swallows with stronger BKA laid smaller clutches, a pattern that was not apparent in early breeders. Regardless of the timing of breeding, birds with stronger BKA fed their nestlings less. Despite a negative association with reproductive effort, we found no association between immunity and reproductive success. We provide evidence that individual tree swallows do not experience some trade-offs equally, and that timing of breeding likely plays a role in how costs of immunity are weighed. To understand how investment in immunity can limit life history traits, we must consider how a variation among individuals influences the relative costs of immunity.